A Randomized Controlled Pilot Exercise and Protein Effectiveness Supplementation Study (EXPRESS) on Reducing Frailty Risk in Community-Dwelling Older People. Issue 1 (2nd January 2021) - Jadczak, Agathe Daria; Visvanathan, Renuka; Barnard, Robert; Luscombe-Marsh, Natalie
Abstract: This pilot study aimed to examine the feasibility and effectiveness of a 6-months multi-component exercise program combined with twice daily consumption of either rice (RicePro) or whey-based (WheyPro) protein supplements (2 × 20 g of protein) on gait speed, grip strength and physical performance in community-dwelling pre-frail and frail older adults. Secondary outcomes included: frailty score, muscle mass, quality of life, nutritional intake, cognitive performance, depression and physical activity levels. A total of 70 participants (mean age 73.34 ± 6.85 years) were randomly allocated to either RicePro ( n  = 36) or WheyPro ( n  = 34). No adverse events were reported in regards to the exercise, however, several gastrointestinal symptoms were noted with the whey protein causing two-fold more symptoms compared to the rice protein. No differences were found between the groups ( p  > 0.05), except the total consumed energy (kJ) ( p  = 0.014) and fat (g) ( p  = 0.012) which was significantly lower in WheyPro. The results indicate that the quality of protein may not be as important as long as a sufficient amount is consumed.